2013
DOI: 10.1002/2013ja019319
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale and large‐scale variability in high‐latitude ionospheric convection: Dominant modes and spatial/temporal coherence

Abstract: [1] Empirical orthogonal function (EOF) analysis, a variant of principle component analysis, is applied to 20 months of plasma drift data from the Super Dual Auroral Radar Network radars in the high-latitude region of the Northern Hemisphere. Dominant modes of ionospheric electric field variability are identified and the spatial and temporal coherence of this variability is quantified. The first three modes of variability, which, together with the mean, account for 50% of the observed squared electric field (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(70 citation statements)
references
References 45 publications
5
65
0
Order By: Relevance
“…EOFs of the Hall and Pedersen conductances, herein represented using the polar cap spherical harmonics basis, are obtained by a sequential nonlinear regression analysis of observations along DMSP satellite trajectories and ordered by their variance. These EOFs and their amplitudes can be used to describe the spatial and temporal coherence of the Pedersen and Hall conductances in a manner similar to that reported by Matsuo et al [, ] and Cousins et al [, ] for electric field variability and Cousins et al [, ] for field‐aligned current variability. Our results allow for improved modeling of the background error covariance needed for ionospheric assimilative procedures [ Richmond and Kamide , ; Matsuo et al , ].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…EOFs of the Hall and Pedersen conductances, herein represented using the polar cap spherical harmonics basis, are obtained by a sequential nonlinear regression analysis of observations along DMSP satellite trajectories and ordered by their variance. These EOFs and their amplitudes can be used to describe the spatial and temporal coherence of the Pedersen and Hall conductances in a manner similar to that reported by Matsuo et al [, ] and Cousins et al [, ] for electric field variability and Cousins et al [, ] for field‐aligned current variability. Our results allow for improved modeling of the background error covariance needed for ionospheric assimilative procedures [ Richmond and Kamide , ; Matsuo et al , ].…”
Section: Introductionmentioning
confidence: 77%
“…Some aspects of the correlations are noteworthy: Since indices represent imperfect proxies for ionospheric phenomena, which themselves often respond in a nonlinear manner to many different drivers, we are encouraged by the fact that several of the correlation coefficients between the indices and higher‐order EOFs are greater than 0.5. The more localized the EOF features, the less likely they are to be correlated with the parameters. This is why correlations generally decrease for higher‐order EOFs [ Matsuo et al , ; Cousins et al , ]. Thus, low correlations do not necessarily mean a relationship does not exist.…”
Section: Resultsmentioning
confidence: 99%
“…The assimilative approach taken in this study provides a framework for optimally combining the different observations, as well as background statistical models, taking into account the error properties of the various sources of information. In particular, the procedure developed in this study incorporates statistical error properties obtained through empirical orthogonal function (EOF) analysis of both SuperDARN data (described by Cousins et al []) and of AMPERE data (described in the companion paper Cousins et al [], referred to hereafter as Paper 1).…”
Section: Introductionmentioning
confidence: 99%
“…However, more than 50% of the observations are in the dayside where we see only a weak dependency on AE and no dependency on IMF B z . The work by Cousins et al () also found a weak correlation with AE index and almost no correlation with IMF B z for smaller spatial (<1,000 km) and shorter temporal scale (a few tenth minutes) variability in the electric field.…”
Section: Discussionmentioning
confidence: 92%